ISLAMIC LAW PERSPECTIVE ON THE POLITICS OF CRIMINAL LAW IMPLEMENTING ADDITIONAL CRIMINAL SANCTIONS REVOCATION OF POLITICAL RIGHTS FOR CORRUPTORS IN INDONESIA - Doni Hendra Lubis (Proceeding International Seminar of Islamic Studies, 2023)
Islam is a perfect religion, all commands and prohibitions are strictly regulated in the Al-Quran and As-Sunnah, including strict prohibitions against acts of ghull (corruption) which Allah SWT hates so much and gets severe sanctions against the creators. In national law, the perpetrators of criminal acts of corruption are also subject to punishment, namely criminal sanctions for the revocation of political rights after the Constitutional Court decision Number: 4/PUUVII/2009, then it seems that the criminal law politics approach to eradicating corruption must be subject to maximum sanctions, seen in the Constitutional Court Decision Number 87/ PUU-XX/2022 in the judicial review of Article 240 paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections which in fact has implications for the revocation of political rights for perpetrators of criminal acts of corruption who must wait a period of 5 (five) years from completing criminal penalties so that they can nominate themselves or be nominated in general elections and for perpetrators of corruption more than once, this has implications for permanently hampering their ability to run for and or be nominated in general elections. The method in this research is normative legal research, namely research conducted by researching literature (secondary data) or library law research. And this research is descriptive analysis in nature where research that is descriptive analysis is a research that describes, examines, explains and analyzes a legal regulation or judge's decision that has permanent legal force. Where in this study the rules of law, library materials, and judges' decisions become material for conducting research in order to obtain academic truth.